Poly(acrylonitrile-co-butadiene-co-styrene) Reinforced with Hollow Glass Microspheres: Evaluation of Extrusion Parameters and Their Effects on the Composite Properties. (10th July 2016) - Cunha, Marina Panozzo; Gonella, Laura Berasain; Poletto, Matheus; Grisa, Ana Maria Colon; Brandalise, Rosmary Nichele
Abstract : Hollow glass microspheres (HGMs) filled poly(acrylonitrile-co-butadiene-co-styrene) (ABS) composites were prepared by means of a twin-screw extruder. S038 HGMs were incorporated at different percentages of 2.5, 5.0, and 7.5 wt%. The HGMs were added into the twin-screw extruder at two different feeding zones, and the effect of HGMs loading and specific feeding zone addition on the composites produced was evaluated with regard to morphological, thermal, rheological, physical, and mechanical properties. As a result, the composite density was reduced while the thermal stability, storage modulus, complex viscosity, and tensile and flexural modulus were improved when compared with the ABS matrix. The results also indicate that the addition of 5.0 wt% of HGMs at the feeding zone closer to the die maintains the integrity of the HGMs and promotes composites with higher mechanical properties and lower density when compared with the composites obtained with the addition of HGMs closer to the hopper.